ANALISIS YURIDIS PERLINDUNGAN HUKUM KEPADA KONSUMEN DARI DAMPAK NEGATIF PRODUK MAKANAN YANG MENGANDUNG ZAT BERBAHAYA - Fransisco, Wawan (Law Journal (LAJOUR), 2020)
Food or food has a very important role for human life, because without human food can not survive to carry out daily activities. The problems that arise in the community that is the number of food beradar food products that cause negative impacts. The use of food engineering products can cause risks or negative impacts on human health, ethics or religion, even the environment. This is of course detrimental to consumers as those who consume food engineering products. Normative legal writing method because it examines the laws and regulations, literature, and journals as well as papers relating to the material examined, which consists of the type of data obtained in this study is secondary data that is data obtained from library research and documentation, which is a the results of research and processing of other people, which are already available in the form of literature or documentation. This research aims to determine the form of legal protection to consumers from the possible negative impacts of food engineering products and the task of guiding and supervising the implementation of consumer protection, the role of government also shapes what is meant by National Consumer Protection Agency (BPKN), Commercialization of food product engineering technology raises a variety of problems related to the responsibilities of business actors, Legal Sanctions against Business Actors If Consumers Are Losing Due To Consuming Foods That Contain Substance Dangerous, and government agencies.